LIMITASI HUBUNGAN SEKSUAL PASANGAN SUAMI ISTRI MENJADI PEMERKOSAAN DALAM PERKAWINAN - Arini Zubaidah, Dwi (USRATUNA: Jurnal Hukum Keluarga Islam, 2024)
Marital rape is the act of someone forcing their partner to have sexual relations by force/without consent. This type of research is doctrinal law which examines the concept of rape in marriage. Researchers use a conceptual approach that focuses on norms, theoretical principles of marriage law, statutory regulations and provisions of Islamic law. This research shows that marital rape can be viewed from a paradigm, legal and psychological perspective. Even though marital rape is regulated in UUPKDRT and Criminal Code Law no. 1 of 2023, but it is still difficult to stop because it is only a criminal act in a complaint offense. Islamic marriage law views rape in marriage as based on two basic principles of good relations between husband and wife, mutual consent and deliberation and supporting evidence for its hujjah in the form of hadith. A married couple's sexual relationship can turn into marital rape if there is coercion involved.